Efek Antiproliferatif Pentagamavunon-O Terhadap Sel Myeloma: Atniproliferative Effect of Pentagamanunon-O on Myeloma Cells - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Pentagamavunon-0 or PGV-0 [2,5-bfs-(4'-hydroxy-3'-methoxybenzylidene)-cyclopentanone] is an analogue of curcumin (1,7-te-(4'-hydroxy-3'-methoxyphenyl)-l,6-heptadiena-3,5-dion). The aim of this research is to observe the cytotoxicity and antiproliferative effect of curcumin and PGV-0 againts cancer cell lines, namely myeloma cells. Antiproliferative properties of both compounds were tested by doubling time analysis againts myeloma cells. The result showed that both compounds possesed an antiproliferative properties as indicated by the prolongation of the doubling time and probably induce apoptosis to the cells. However, the prolongation effect of PGV-0 to the growth rate of the cells were higher than curcumin did. These results indicate that the cytotoxic and antiproliverative properties of PGV-0 are better than curcumin. The results also showed that PGV-0 possesed cytotoxic effect againts myeloma cells with ICM values of 8.72 ^M. Curcumin showed IC^ values of 19.55 iM. 0. Keywords: pentagamavunon-0 -myeloma cells